Analysis of triggering agricultural insurance based on climate simulations in the state of Paraná - Souza, Patricia B. de; Boninsenha, Igor; Braga, Gustavo Bastos; Mantovani, Everardo C. (Brazilian Journal of Production Engineering, 2020)
Despite the wide technological development that has occurred in the last decades, Brazilian agribusiness is still susceptible to climatic weather conditions that can cause significant losses in crop productivity in certain areas. In order to provide more security to rural producers, the government has historically adopted some risk mitigation systems. One of the most common is that of subsidized agricultural insurance, which in Brazil since 2003, has been improved through the creation of the Rural Insurance Award (PSR) Subsidy Program. As this system is a strategic tool for both producers and the government, having knowledge of the probability of a certain climatic weather and the ability of these to cause damage to crops, makes the agricultural insurance system more effective in national agricultural development. In this way, in the present work, the activations of agricultural insurance in the municipalities of Maringá, Londrina and Irati in the state of Paraná were analyzed, comparing with planting simulations on different dates using the IrriPlus® software. The results obtained highlight the importance of the PSR for both rural producers and the public authorities and conclude that crop simulations have ample potential for predicting occurrences of weather conditions during the crop cycle, which can improve the efficiency of agricultural insurance.